Complexions at the Electrolyte/Electrode Interface in Solid Oxide Cells. Issue 18 (21st August 2021) - Türk, Hanna; Schmidt, Franz‐Philipp; Götsch, Thomas; Girgsdies, Frank; Hammud, Adnan; Ivanov, Danail; Vinke, Izaak C.; de Haart, L.G.J. (Bert); Eichel, Rüdiger‐A.; Reuter, Karsten; Schlögl, Robert; Knop‐Gericke, Axel; et al.
Abstract: Rapid deactivation presently limits a wide spread use of high‐temperature solid oxide cells (SOCs) as otherwise highly efficient chemical energy converters. With deactivation triggered by the ongoing conversion reactions, an atomic‐scale understanding of the active triple‐phase boundary between electrolyte, electrode, and gas phase is essential to increase cell performance. Here, a multi‐method approach is used comprising transmission electron microscopy and first‐principles calculations and molecular simulations to untangle the atomic arrangement of the prototypical SOC interface between a lanthanum strontium manganite (LSM) anode and a yttria‐stabilized zirconia (YSZ) electrolyte in the as‐prepared state after sintering. An interlayer of self‐limited width with partial amorphization and strong compositional gradient is identified, thus exhibiting the characteristics of a complexion that is stabilized by the confinement between two bulk phases. This offers a new perspective to understand the function of SOCs at the atomic scale. Moreover, it opens up a hitherto unrealized design space to tune the conversion efficiency. Abstract : By combining transmission electron microscopy and Monte Carlo simulations, a complexion is found to be formed between the yttria‐stabilized zirconia (YSZ) electrolyte and lanthanum strontium manganite (LSM) air electrode during the sintering process of solid oxide cells. This nanometer‐wide interlayer of self‐limited width is characterized by partial amorphization and compositional gradients and offers a new perspective to understand the functionality of these cells.